STEM Education and Labor Needs: Engineering Graduates in Ethiopia - Teshome, Asmera; Oumer, Jeilu (Universitas Terbuka, 2024)
This study examined the alignment between the supply of STEM skills by higher education institutions and the demand for these skills in the labor market in Ethiopia, employing a mixed-methods approach. Quantitative data from 275 respondents were analyzed using mean, standard deviation, and paired sample t-tests, while thematic analysis was applied to qualitative data. The results revealed significant mismatches between the skills provided by educational institutions and those required by the labor market, with the greatest disparities found in generic skills, followed by technical and interpersonal skills, and the least in discipline-specific skills. The study highlights the urgent need for higher education institutions to enhance their collaboration with industry stakeholders to develop curricula that effectively address these gaps. Recommendations include conducting regular market needs assessments, integrating external expert lectures, and applying project-based learning to foster critical and innovative thinking skills among students, preparing them more effectively for employment.